2014
DOI: 10.1111/1750-3841.12501
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of the Hepatotoxic Compound Sophoraflavanone G in Rat Liver Microsomes

Abstract: Our study aimed at investigating the metabolic characteristics of sophoraflavanone G (SFG), one of the hepatotoxic constituents of Sophora flavescens, in rat liver microsomes (RLMs). SFG was metabolized to 3 phase I metabolites, di-hydroxylated SFG (M1), mono-hydroxylated SFG (M2), dehydrogenated product of mono-hydroxylated SFG (M3) and 3 SFG glucuronides (M4, M5, and M6) by RLMs. The formation kinetics of M2 conformed to biphasic kinetics in RLMs. The formation kinetics of M4 and M5 best-fitted the Hill equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…It is well known that the pharmacokinetic and bioavailability study of a bioactive constituent can help us to understand its in vivo behavior and actions . To date, a few studies have investigated the metabolism and pharmacokinetics of a single component of the prenylated flavonoids in S. flavescens . However, the treatment of diseases by traditional Chinese medicine is based on the interactions of multiple ingredients .…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the pharmacokinetic and bioavailability study of a bioactive constituent can help us to understand its in vivo behavior and actions . To date, a few studies have investigated the metabolism and pharmacokinetics of a single component of the prenylated flavonoids in S. flavescens . However, the treatment of diseases by traditional Chinese medicine is based on the interactions of multiple ingredients .…”
Section: Introductionmentioning
confidence: 99%
“…Owing to very small amounts of M2-M7 being formed, only the major metabolite M1 was prepared using a preparative HPLC, and quantitatively determined using the calibration curve. The hill coefficient (h) was 1.48, indicating that a positive cooperative reaction had occurred between irisflorentin and RLMs (Chen et al, 2014). The regression equation was y = 0.0173x + 0.0053 and the correlation coefficient (r 2 ) was 0.9974.…”
Section: Kinetics Of Irisflorentin Metabolism By Rlmsmentioning
confidence: 96%
“…9, inset) (Moreira et al, 2013;Marques et al, 2014). The hill coefficient (h) was 1.48, indicating that a positive cooperative reaction had occurred between irisflorentin and RLMs (Chen et al, 2014). Those two particular types of rate substrate concentration curves, sigmoidal and convex, were characteristic that the metabolism of irisflorentin was atypical Michaelis-Menten kinetics (Houston and Galetin, 2003).…”
Section: Kinetics Of Irisflorentin Metabolism By Rlmsmentioning
confidence: 97%
“…Metabolism is an important pharmacokinetic process that influences the biological activity and toxicity of drugs in vivo (13). Certain components of a drug can be converted to toxic metabolites, while other components are transformed to non-toxic metabolites (14). It has been reported that when taken orally, the majority of OMT is transformed into the more absorbable metabolite MT by intestinal bacteria in the gastrointestinal tract (15).…”
Section: Introductionmentioning
confidence: 99%